Transforming Classroom Management as the Key to Increasing Student Learning Interest - Mar'atul Azizah; Ahmad Budiyono; Abd. Rozaq; Arif Rahman Hakim (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to describe integrative classroom management that is oriented towards increasing students' interest in learning at MTs At-Taufiq Bogem Grogol Jombang. Using a descriptive qualitative approach, data were collected through non-participant observation, structured interviews, and documentation. Data validity was tested through triangulation of sources, time, and techniques. Data analysis adopted the interactive model of Miles and Huberman. The results showed that classroom management was implemented through planning, implementation, and evaluation functions. Planning involved meetings with teachers and staff held twice a year. Implementation created a friendly atmosphere between teachers and students, although there were challenges in managing male students due to environmental factors. Evaluation was carried out through supervision by the head of the madrasah on innovation and learning tools. Students' interest in learning after classroom management increased, reflected in indicators of the desire to know or have something, objects or activities that they liked, types of activities to achieve things they liked, and efforts to realize desires. The contribution of this study lies in the integration of the social-constructivist approach and self-determination theory in the development of a classroom management model, the development of contextual learning interest measurement instruments, and a classroom management implementation model specifically designed for Islamic educational institutions